Heterogeneity and efficacy of immunotherapy in multiple cancer: insights from a meta-analysis - Weidong Wu; Bin Liu; Qing Zhang; Xiaojuan Zhang; Pengya Feng; Yongliang Jia; Xia Xue (Biological Procedures Online)
Abstract Background Immunotherapy has been recognized as a significant advancement in cancer treatment by promoting the body’s immune system to identify and eliminate cancer cells more effectively. Unlike conventional therapies, immunotherapy can enhance the natural capabilities of human immune system. Chimeric Antigen Receptor T-cell (CAR-T) therapy involves genetical-modified T-cells from patients to better catch and attack cancer cells. Up to date, CAR-T therapy has shown particular promise in treating certain types of leukemia and lymphoma, highlighting the transformative potential of immunotherapy. Results Literature data search using PubMed, CNKI, and Wanfang were searched to collect eligible studies up to January 2025. The primary outcomes of complete response rate (CRR), objective response rate (ORR), dead rate (DR), and other adverse reactions were evaluated. Secondary outcomes (CRR, ORR, and DR) of subgroup analysis from different cancer types, origins, and outcomes for survival rate were analyzed for our final results. A total of 649 studies were initially identified through database searching. After removing duplicates and non-clinical cancer studies, 32 eligible studies were included in this work. The pooled data included 819 patients for objective response rate (ORR), 843 patients for complete response rate (CRR), and 868 patients for dead event. In the included studies, 24 reported ORR data, revealing an objective response rate of 84.86% (695/819) with little heterogeneity (OR: 0.87, 95% CI 0.80–0.91, P = < 0.01, I2 = 61%); 24 studies showed a CRR of 65.30% (491/843) with significant heterogeneity (OR: 0.58, 95% CI: 0.43–0.72, P < 0.01, I2 = 84%); 27 studies showed a mortality rate of 23.73% (206/868) with significant heterogeneity (OR: 0.19, 95% CI: 0.11–0.32, P < 0.01, I2 = 77%). Subgroup analysis based on cancer type revealed that ORR was higher in multiple myeloma (86.77%, 400/461) compared with leukemia (84.92%, 259/305) and lymphoma (67.92%, 36/53). In parallel, heterogeneity observed based on case origins suggested that Chinese cases showed significantly higher ORR, CRR, and survival rates compared with American ones. Conclusions This meta-analysis provides valuable insights into the potential of immunotherapy, particularly CAR-T, in cancer treatment. Findings showed the different efficacy and safety of immunotherapy in treating multiple cancers, with various objective response rates. Continued studies from more trials with different populations are needed to optimize their efficacy in further cancer treatment and precision medicine.